Effect of harvest age on nutritive value of king grass (Pennisetum purpureum) measured using conventional and NIRS methods - Amahd Unonis, Muhamad Nizam (2015)
King Grass or Pennisetum purpureum is common forage that has been used as animal feed. It is a tropical perennial grass and native to the African grassland. The experiment was conducted to study the effect of harvest age on nutritive value of King Grass. The objective of this experiment is to identify the differences in nutritive value of King Grass according to its harvest age and to identify the differences in the analysis of nutritive value based on chemical method and Near Infrared Spectroscopy (NIRS). This experiment was conducted at Field 2, Universiti Putra Malaysia (UPM) in a period of 4 months starting on March until June 2014. The experiment was conducted using Randomized Complete Block Design (RCBD) with 4 replications. Three ages of harvest were used as a treatment which is 3, 5 and 7 weeks. Conventional and NIRS methods were used to measure the Crude protein (CP), Acid detergent fiber (ADF) and Neutral detergent fiber (NDF) of King Grass. The result showed that the NDF and ADF value were increased as the harvest age increased. Crude protein concentration decreased with later harvests. Based on the result of this experiment the best time to harvest King Grass was at week 5 because it gave the optimum value in term of quality and yield. The nutritive quality measurements using the NIRS technique was not correlated with that of the chemical method as a result of poor calibration of the equipment.